2018
DOI: 10.1038/s41598-018-23774-9
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamics of stage-specific transcription factor binding during thymocyte development

Abstract: In vertebrates, multiple transcription factors (TFs) bind to gene regulatory elements (promoters, enhancers, and silencers) to execute developmental expression changes. ChIP experiments are often used to identify where TFs bind to regulatory elements in the genome, but the requirement of TF-specific antibodies hampers analyses of tens of TFs at multiple loci. Here we tested whether TF binding predictions using ATAC-seq can be used to infer the identity of TFs that bind to functionally validated enhancers of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Given that Gata3 is expressed throughout T cell development in the thymus and in mature ILCs and differentiated T cells in the periphery, we next evaluated chromatin accessibility in these populations using publicly available ATAC-seq data (2,37). The distal Gata3 +674/762 region was conspicuously inaccessible in thymocytes, while Gata3 +278/285 accessibility persisted throughout T cell development, consistent with previously reported experiments (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 78%
“…Given that Gata3 is expressed throughout T cell development in the thymus and in mature ILCs and differentiated T cells in the periphery, we next evaluated chromatin accessibility in these populations using publicly available ATAC-seq data (2,37). The distal Gata3 +674/762 region was conspicuously inaccessible in thymocytes, while Gata3 +278/285 accessibility persisted throughout T cell development, consistent with previously reported experiments (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 78%
“…We obtained publicly available ATAC-seq data derived from cell types sorted ex vivo and brain single-nuclei analyses from mice (Supplemental Table S1; Mo et al 2015;Matcovitch-Natan et al 2016;Gray et al 2017;Hughes et al 2017;Hosoya et al 2018;McClymont et al 2018;Preissl et al 2018). In total, we obtained 25 mouse ATAC-seq open chromatin region (OCR) data sets encompassing subclasses of six broader cell types (dopaminergic neurons, excitatory neurons, glia, inhibitory neurons, retina cells, and T cells) (Supplemental Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether the early stages of the iNKT maturation program were critical for determining the chromatin accessibility profile of mature iNKTs, we performed ATAC-seq in ST0, ST1, and mature NKT1 (sorted as Tetr + TCRβ + CD24 − CD44 + NK1.1 + ) cells. To exclude loci that may be open transiently in ST0 cells due to positive selection and TCR signaling, we restricted our analysis in loci that were more accessible in mature NKT1 cells as compared to DP thymocytes 31 (iNKT-related regions). Our results showed that these regions were already accessible in ST0 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%